Markups, production, and income distribution under segmented asset markets - Enders, Zeno (Bonn Econ Discussion Papers, 2009)
A model of segmented asset markets is developed, in which varieties of consumption bundles are purchased sequentially. By this, a non-degenerate heterogeneity in wealth and the effective elasticity of substitution across households arises, affecting optimal markups chosen by firms. Furthermore, the model features an internal propagation mechanism that stems from the slow dissemination of newly injected money via second-round effects. These mechanisms generate a short-term inflation-output trade-off, a liquidity effect, countercyclical markups, procyclical profits and wages after monetary shocks. Furthermore, the responses of output, inflation, hours worked, velocity, and profits are quantitatively in line with VAR evidence. -- Limited Participation ; Countercyclical Markups ; Liquidity Effect ; Segmented Asset Markets